Warlordism, insurgency and public opinion: explaining civil war in Afghanistan - Bhatia, J (2019)
Current explanations for civil war are divided between grievance and opportunity-based paradigms. This thesis bridges these two theoretical schools by emphasizing elite fragmentation as an understudied variable in the onset and spread of insurgent violence. The three articles of this thesis examine these dynamics through the case study of the post-2001 civil war in Afghanistan. First, I compare variations in political violence within two neighboring provinces of northern Afghanistan, demonstrating how fragmentation between armed groups produces heightened grievances amongst civilians, incentivising them to defect to insurgent groups. Second, I show additional evidence challenging the legitimacy of armed commanders through a conjoint experiment demonstrating that Afghan citizens have strong preferences for leaders who are young and highly educated over older leaders with military experience. Third, I examine why attempts to redress public grievances with large injections of foreign aid have largely failed to win over the population in insecure areas with a case study of the National Solidarity Program in Wardak province. Together, the chapters of this thesis contribute to current literature on civil war while suggesting important policy implications for how the international community should engage in civil wars in Afghanistan and elsewhere.